Analisis Muka Air Banjir Sungai Segeri Pada Persilangan Jalur KA Lintas Makassar-Pare-Pare - Harianto, Dwi Yuli; Yusuf, Andi Rumpang; Badrun, Burhanuddin (Program Studi Teknik Sipil Universitas Bosowa, 2023)
The construction of the Makassar-Parepare railroad line that crosses Pangkep district which intersects with the Segeri river is at an altitude of +10,229 m. The Segeri River is in the Pangkajene Watershed area with the Segeri Sub-watershed which has an area of 96,011 Km2. Segeri river flood discharge was calculated using the Nakayashu method with discharge values with return periods of 2,5,10,25 and 50 years of 102.27 m3/second, 125.99 m3/second, 146.06 m3/second,176.89 m3/second and 204.28 m3/second. The flood water level of the Segeri river at discharge with a 50year return period is at an elevation of +3.07 m, so that the flood water level of the Segeri river is below the railroad elevation